Pengaruh Motivasi Terhadap Produktivitas Kerja Karyawan Pada UMKM Batik - Dwirainaningsih, Yustiana (JURNAL LITBANG KOTA PEKALONGAN, 2022)
This research was conducted in order to determine the extent to which work motivation, both internal and external motivations affect work productivity in micro, small and medium enterprises engaged in batik. The method we use is a qualitative descriptive method and the respondent data is 48 people who have a batik company (Tobal Batik). Increasing employee productivity is the responsibility of each agency. Through leaders, employees try their best to further increase their potential. Work productivity remains maximal, for the internal motivation variable is 2.825 while ttable is 1.678 so that it can be concluded that tcount (2.825) > ttable (1.678) and a significant value of 0.007 .0.1, automatically the hypothesis obtained is the existence of productivity at H? is accepted. For the tcount of the external motivation variable of 3,875, so it can be concluded that tcount (3.875) > ttable (1.678) and a significant value of 0.000 <0.1 so the hypothesis obtained that there is a significant influence of internal motivation on the productivity of H? is accepted. Currently the company’s productivity returns to normal along with the number of orders or demand for goods. Basically, motivation is very important in supporting the productivity of work carried out by employees. Keywords: Internal motivation, external motivation, work productivity, small and medium entreprise (SME)